Association between dietary patterns and depressive symptoms in adult women living in Tehran (2013) - M. Lahouti; R. Zavoshy; M. Noroozi; B. Rashidkhani; R. Rostami (The Journal of Qazvin University of Medical Sciences, 2015)
Background: Depression is one of the most common mental illnesses. Few studies have investigated the association between dietary patterns and depression in developing countries. Objective: The aim of this study was to determine the association between dietary patterns and depressive symptoms in adult women living in Tehran in 2013. Methods: This cross-sectional study was carried on 217 women aged 20-45 years attending health centers in the north and west of Tehran in 2013. The subjects were selected by systematic cluster sampling method. Data were collected through demographic, food frequency, and physical activity questionnaires and the beck depression inventory. Major dietary patterns were identified by factor analysis and their association with depressive symptoms was assessed by logistic regression analysis. Findings: The prevalence of depressive symptoms was 63.2% in the studied women. Two major dietary patterns were identified (healthy and unhealthy). After adjusting for confounders, subjects with higher scores in the unhealthy dietary pattern had higher odds (OR=2.21, P=0.01) of depressive symptoms; but the healthy dietary pattern was not associated with depressive symptoms. Conclusion: With regards to the results, it seems that the unhealthy dietary pattern is associated with the risk of depression in women.